Cradles of the Reich : a novel - Coburn, Jennifer, 1966- (Sourcebooks Landmark, 2022)
"At Heim Hochland, a Nazi sanctioned maternity home in Bavaria, three women's fates are irrevocably intertwined. Gundi is a pregnant student from Berlin--an Aryan beauty, she's secretly a member of a resistance group. Hilde, only 18, is a true believer in the cause and is thrilled to carry a Nazi official's child. And Irma, a 44-year-old nurse, is desperate to build a new life for herself after personal devastation. All three have everything to lose. Based on untold historical events, this novel brings us intimately inside the women's homes that actually existed in several countries during World War II, when thousands of babies were taken from their mothers to be raised as part of the new Germany. But it proves that in a dark period of history, the connections women forge can carry us through, even driving us to heroism we didn't know we had within us"--